Elucidating the effects of physicochemical variables on the structure, composition and functionality of microbiomes in the Prince Edward Islands - Makhalanyane, Thulani Peter (University of Pretoria, 2020)
Dissertation (MSc (Genetics))--University of Pretoria, 2020.